Impact of teleworking and remote work on business priductivity, retention, advancement, and bottom line - Chandan, Harish C. 1947- (Advances in mrketing, cstomer relationship management, and e-services (AMCRMES) book series, 2024)
The surge in remote and hybrid work arrangements has sparked a paradigm shift in the employment ecosystem. While remote work offers employees the coveted flexibility and freedom from daily commutes, it also introduces challenges such as isolation, reduced visibility, and questions about productivity. Impact of Teleworking and Remote Work on Business: Productivity, Retention, Advancement, and Bottom Line delves into the multifaceted impact of teleworking on businesses, exploring how different organizations grapple with these challenges, drawing on the experiences of industry giants like Google and IBM. It carefully dissects the advantages and disadvantages of teleworking, addressing distractions, cybersecurity concerns, and the polarized nature of remote work across global and skill dimensions.The book presents an exploration of solutions tailored for diverse stakeholders. From strategies to enhance employee productivity and maintain confidentiality to fostering human connections and tackling the challenges faced by new hires, each chapter offers actionable insights. Employers, employees, and management teams will find guidance on creating a collaborative and innovative remote work culture, mitigating distractions, and striking a balance between work and personal life. The suggested topics span the gamut of remote work intricacies, from the relationship between remote work and job satisfaction to strategies for maintaining connections between managers and remote employees. With small, medium, and large companies, government agencies, and universities as the target audience, the book serves as a strategic guide for entities seeking to harness the potential of remote work while mitigating its challenges.